Social Media Marketing and Purchase Intention: Does Relationship Quality, Brand Trust, and Brand Equity Matter? - Al-Hanaan, Muhammad Fadhlillah; Nurhadi, Mochamad; Rachmat, Basuki; Ronny, Ronny (Jurnal Ilmu Manajemen, 2023)
Social media is digital medium for marketing a product. This research aims to measure the influence of marketing on TikTok social media on purchase intention as mediated by relationship quality, brand trust, and brand equity in local Scarlett Skincare products in Indonesia. The sampling technique used purposive sampling of 455 samples. The analysis technique uses Structural Equating Modeling-Partial Least Square (SEM-PLS). The research results show that relationship quality and brand equity can mediate (partial mediation) the relationship between TikTok's social media and purchase intention. However, brand trust was not successful in mediating. The research results also show the positive influence of marketing on TikTok's social media on relationship quality, brand trust, brand equity, and purchase intention. The same results show a positive effect on relationship quality and brand equity on purchase intention. However, the brand is not able to influence purchase intention.